Improving the 3D model accuracy with a post-processing kinematic (PPK) method for UAS surveys. Issue 14 (18th August 2022) - Iizuka, Kotaro; Ogura, Takuro; Akiyama, Yuki; Yamauchi, Hiroyuki; Hashimoto, Takeshi; Yamada, Yudai
Abstract: Numerous studies utilizing unmanned aerial systems (UASs) have been conducted using the structure from motion technique to study regions/objects of interest for various geoscience-related studies. To provide higher model accuracy, ground control points (GCPs) are typically used to aid the image analysis. However, in cases where GCPs are difficult to set or see, such an approach cannot be used. This paper focused on a method for improving a 3D model during the SfM process without the aid of GCPs by utilizing small and lightweight global navigation satellite system (GNSS) devices attached to a multirotor UAS, and an automatic shutter release system was developed for recording the precise time stamp for synchronization. The proposed method was verified as a possible alternative to conventional GCP methods, especially in locations where placing multiple GCPs is difficult or in regions where real-time kinematic (RTK) data are limited due to various limitations (e.g. legal constraints).